Development of an Automatic Portable Calibrator for Tipping Bucket Rain Gauge (TBRG) Using a Load Cell and Simple Water Sensor - Dani Zulfia Rohmah; Jasruddin; Subaer; Bagus Satrio Utomo (Jurnal Penelitian Pendidikan IPA, 2024)
The tipping bucket rain gauge is an automatic rain gauge that can measure rain intensity in mm/hour. Accurate measurement of rain intensity requires calibration of the rain gauge to ensure traceability. Calibration of a tipping bucket rain gauge is related to the volume of water as a calibration medium and time so as to produce a discharge that can be converted into rain intensity. Technological developments can make tipping bucket rain gauge calibration automatic by utilizing an Arduino Mega2560 microcontroller, a load cell and a simple water sensor based on the LM393 comparator IC, and combined with a compact design printed using a three-dimensional printer so that it can be used for ex-situ calibration. The data produced by this tool can be downloaded via the application that was built and produces a file in Excel form.